O jornalista segundo a televisão: uma análise da série The Newsroom - Caldas, Victor Hugo de Carvalho (2016)
In this work we investigate the construction of the character of the journalist in HBO series The Newsroom, comparing it with its cinematographic representation. In addition, we present an overview of the emergence and evolution of the TV series in USA, very popular today and available to the public through a variety of channels, which implies the importance of their understanding.